Sustainable construction site planning and resource efficiency - Elis Mardzianah Mazlan; Asmawan Mohd Sarman; Syazana Jamzain; Nur Fadilah Darmansah; Siti Syarizulfa Kamarudin; Azilah Baddiri; Mark Cyril Francis; Ruzanah Abu Bakar; Shen Ling (RSIS International, 2025)
This study examines sustainable construction site planning and resource efficiency, focusing on industry challenges, sustainability principles, and the role of technology and policy in promoting sustainable practices. The objective is to identify best practices, innovative strategies, and frameworks to enhance resource efficiency and waste management in the construction industry, with a particular emphasis on Malaysia. A systematic literature review was conducted, analysing publications from 2018 to 2024 sourced from Science Direct, ResearchGate, and Scopus. Key areas explored include energy efficiency, waste reduction, the use of sustainable materials, and advancements in green technology. Findings reveal that while sustainable construction is essential, it faces significant challenges including lifecycle assessments, adoption of green building technologies, and the integration of sustainable materials. Policy support and industry collaboration are critical to advancing resource efficiency and ensuring long-term sustainability. Specific results indicate that techniques like Design for Disassembly (DfD), Building Information Modeling (BIM), and the 3R approach (Reduce, Reuse, Recycle) significantly improve waste management and resource optimization. The study concludes with actionable recommendations for policymakers, industry professionals, and educators emphasizing the need to adopt sustainable practices and leverage technological innovations to achieve global Sustainable Development Goals (SDGs) while minimizing environmental impacts.